THE DEPICTIONS OF HELL AND THE DEVIL IN MACEDONIAN FOLKLORE IN XIXTH CENTURY (Philological Studies, 2020)
In this paper we analyze the depictions of hell and the devil in Macedonian folklore from the 19th century by comparing several mediums: folk songs, stories, curses, proverbs, etc. Adam and Eve’s exile from Paradise marks the first internal and external exile in the history of mankind. In light of this, we focus on numerous descriptions of hell as a place full of fire in which sinners are exposed to torments, and of the image of the devil as a master of evil. In this context, we look at different names for hell and the devil that represent social and spiritual apostasy and disapproval of existing ethical and moral norms.
Keywords: Hell; Devil; Last Judgement; XIXth century; folklore; Marko Cepenkov